Diagnostic Potential of Neural Exosome Cargo as Biomarkers for Acute Brain Injury - Goetzl, Laura (Ann Clin Transl Neurol, 2017)
OBJECTIVE: Neuronal exosomes purified from peripheral blood samples have been proposed as diagnostic tool in the setting of acute brain injury but never tested clinically. We hypothesized that exosome protein biomarkers would change over time following acute hypoxic brain injury and would predict response to therapy. METHODS: Synaptopodin (SYNPO), an actin‐associated protein present in postsynaptic spines, was evaluated as a potential biomarker as well as: synaptophysin, neuron‐specific enolase, and mitochondrial cytochrome c oxidase. A secondary analysis was performed on neonatal samples collected at 8, 10, and 14 h after the initiation of therapeutic‐controlled hypothermia for acute hypoxic–ischemic encephalopathy (n = 14). Neuronal exosomes were purified from serum and protein levels were quantified using standard ELISA methods. The primary study outcomes were length of stay (LOS), discharge on seizure medication (DCMED), and composite neuroimaging score (NIS). RESULTS: The slope of change in neuronal exosome SYNPO between 8 and 14 h appeared to be the most promising biomarker for all three clinical study outcomes. SYNPO was highly correlated with LOS (−0.91, P < 0.001). SYNPO increased in 6/8 without DCMED and was worse or neutral in 5/5 with DCMED (P = 0.02). All four neonates with an abnormal NIS had neutral or decreasing SYNPO (P = 0.055). Other candidate biomarkers were not associated with outcomes. INTERPRETATION: This report provides the first clinical evidence that neural exosomes turn over rapidly enough in the peripheral circulation to be used as a “troponin‐like” test following acute brain injury. Optimal sampling and biomarkers likely vary with type of brain injury.